Hubungan Respon Time Petugas Ambulans Gawat Darurat dengan Keberhasilan Penanganan Pasien Cardiac Arrest: Correlation between Response Time of Emergency Ambulance Officers and Successful Management of Cardiac Arrest Patients - Mitcel, Handoyo (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: According to the World Health Organization (WHO) states that heart attack is still the number one killer of humans in developed and developing countries killing 60 percent of all deaths. Signs of cardiac arrest, namely there is no reaction from the patient, there is stopping breathing or shortness of breath, and no vibrations are felt within 5 seconds. One indicator of the success of a medical emergency response is the speed in providing adequate assistance for emergency patients. One of the efforts to deal with the increasing cases of medical emergencies and disasters is to provide Emergency Medical Services and prepare healthcare workers.  Methods: This research is a type of quantitative correlation analysis. The research design used is a cross-sectional or cross-sectional study. The population in this study were 68 cardiac arrest patients in the North Jakarta area using the AGD ambulance of the DKI Jakarta Health Office. The sampling technique used was accidental sampling. So, the sample in this study was 30 patients. The research instrument used an observation sheet. Researchers used the Chi-Square Test. .Results: The relationship between the response time of emergency ambulance staff and the successful handling of cardiac arrest patients obtained a p-value = 0.009, meaning that the p-value <α (0,05). Discussion: There is a relationship between the response time of emergency ambulance staff and the successful handling of cardiac arrest patients. Cardiac arrest is one of the emergency cases that can be life-threatening and requires a fast response time to be given good treatment, without cardiac compression or defibrillation, death will occur within minutes.